Service quality and customer satisfactory at Fidelity Bank, Ghana - Manu, Philip Appiah (University of Cape Coast, 2024)
This study was aimed to examined the service quality and customer satisfaction at Fidelity Bank, Ghana. The “study employed the explanatory research design since the study tested the relationship between the various variables. The data collection instruments were questionnaire. The study employed the quantitative research approach. The simple random sampling technique was used in selecting a respondent of 300. Descriptive statistics and structural equation model were employed to analyse the objectives of the study. The study found that there was a positive and significant relationship between tangibles quality and customer satisfaction at Fidelity Bank. Also, the study found that there was a positive and significant relationship between reliability quality and customer satisfaction at Fidelity Bank. The study found that there was a positive and significant relationship between responsiveness quality and customer satisfaction at Fidelity Bank. The study also found that there was a positive and significant relationship between assurance quality and customer satisfaction at Fidelity Bank. There was no positive and significant relationship between empathy quality and customer satisfaction at Fidelity Bank. The study recommended that management of Fidelity Bank must invest in employee training.
xii,83p;,ill
Keywords: Service quality; Customer Satisfaction; Fidelity Bank